Single Subcutaneous Ketamine Dose Followed by Oral Ketamine for Depression Symptoms in Hospice Patients: A Case Series. (3rd April 2021) - Latuga, Natalie M.; Luczkiewicz, Debra L.; Grant, Pei C.; Levy, Kathryn; Hansen, Eric; Kerr, Christopher W.
Abstract: Management of depression symptoms in hospice patients is complicated by the fact that an appropriate trial of antidepressant therapy requires 4–6 weeks and most hospice patients receive hospice services for less than 8 weeks. Intravenously administered ketamine has been shown to produce rapid improvement in depression symptoms but is not an ideal route for hospice patients and oral ketamine appears to have a slower onset of antidepressant activity. We present a case series that illustrates the use of a single subcutaneous dose of ketamine (0.5 mg/kg) followed by daily oral ketamine (0.5 mg/kg daily) therapy to manage depression symptoms in three hospice patients. Clinical improvement of depression symptoms occurred quickly for all patients as measured by the PHQ-4, numeric ratings, and subjective reporting. A single subcutaneous dose of ketamine followed by oral therapy presents itself as an option to quickly reduce depression symptoms in hospice patients that do not also require additional pain management. Combining the use of the subcutaneous and oral routes takes advantage of the possibly faster onset, home administration, and milder side effects than intravenous dosing. Prospective studies are needed to determine which dosing strategy would be the most beneficial for hospice patients.